Yahoo CEO giant Marissa Mayer : remaking an internet giant - Mayer, Marissa, 1975-; Levy, Steven; Safari eBooks; WIRED Business Conference in partnership with MDC(X) Partners ([Place of publication not identified] : FORA.tv, 2013)
"Marissa Mayer, President & CEO, Yahoo!, discusses how she plans to remake an internet giant. Mayer is in conversation with Steven Levy, Senior Writer, WIRED."--Resource description page.
Title taken from resource description page (viewed July 2, 2015)
Presenter, Eric Hunsader.
Keywords: Yahoo! Inc; Internet industry -- Management; Executive ability; Electronic books